A Review on Extraction, Multi-Industrial Applications and Sustainable Valorization of Apple Pomace: Review Article (Journal of Pharma Insights and Research, 2026)
Pectin is an important structural polysaccharide within apple cell walls, primarily composed of α-(1→4)-linked D-galacturonic acid units. As global industrial demand for natural, functional hydrocolloids rises, apple pomace a major byproduct of the juice and cider industries emerges as a critical renewable resource. Traditional pectin recovery relies on hot acid hydrolysis, which often compromises molecular integrity and results in substantial environmental footprints due to hazardous effluent generation. A transition toward green extraction technologies, including enzyme-assisted (EAE), ultrasound-assisted (UAE), microwave-assisted (MAE), and subcritical water (SWE) extractions, offers pathways to higher yields and preserved functional attributes. These methodologies utilize acoustic cavitation, electromagnetic radiation, or enzymatic specificity to disrupt the plant matrix with reduced energy inputs and chemical consumption. Structural nuances, such as the degree of esterification and molecular weight distribution, dictate the gelling and emulsifying performance of the isolated polymer. Sophisticated optimization tools, specifically response surface methodology (RSM) and artificial intelligence (AI) models like artificial neural networks, facilitate the prediction of extraction kinetics and the refinement of processing parameters. Beyond food texture engineering, apple-derived pectin serves as a bioactive substrate in pharmaceutical drug delivery, tissue engineering, and sustainable cosmetic formulations. The integration of these advanced processes supports circular bioeconomy objectives by transforming agro-industrial waste into high-value biopolymers